Navigation using OEM GPS module and magnetic sensor - Wang, Jun. (2008)
This project is to build a Navigation System with tracking function by using a combination of several modern technologies. It includes GPS - The Global Positioning System, DR - Dead Reckoning method, and GSM - The Global System for Mobile Communication. This dissertation firstly gives an introduction to the project motivation, objectives and the major contributions, and also provides a background on GPS system, Dead Reckoning method and GSM system. Secondly, the dissertation gives the descriptions of the theory behind the software and hardware implementation, and the details of hardware integration, as well as explains the software structure, interfaces protocol and programming. The dissertation includes results and discussions of the project, and also figures out the problems faced throughout the project and the recommendations. In the end, the conclusion from this project and the suggestions for further improvement are presented.